The Application of Audio Recording in a Smartphone to Assist Students' Speaking Skills in Senior High School - Santika, Nathanael (RETAIN, 2021)
Abstract In this study, the researcher is interested in knowing how the teacher uses the audio recording strategy to help students with their speaking skills. Students can use the audio recording to analyze their speaking skills and explore how to speak fluently with their classmates. Since the audio recording contains pauses and repetitions, students are better prepared to say confidently. As a result, it would encourage students to use English more often. The data was gathered through observation and communicating rubric performance. The results found that the teachers used the audio recording to assist their speaking activities. The researcher hopes that implementing this strategy will help the students with their speaking abilities. Keywords: Speaking skills, learning media, audio recording.